High levels of gene flow and genetic diversity in Irish populations of Salix caprea L. inferred from chloroplast and nuclear SSR markers - HODKINSON, TREVOR (My University, 2014)
Background Salix caprea is a cold-tolerant pioneer species that is ecologically important in Europe and western and central Asia. However, little data is available on its population genetic structure and molecular ecology. We describe the levels of geographic population genetic structure in natural Irish populations of S. caprea and determine the extent of gene flow and sexual reproduction using both chloroplast and nuclear simple sequence repeats (SSRs). Results A total of 183 individuals from 21 semi-natural woodlands were collected and genotyped. Gene diversity across populations was high for the chloroplast SSRs (HT = 0.21-0.58) and 79 different haplotypes were discovered, among them 48% were unique to a single individual. Genetic differentiation of populations was found to be between moderate and high (mean GST = 0.38). For the nuclear SSRs, GST was low at 0.07 and observed heterozygosity across populations was high (HO = 0.32-0.51); only 9.8% of the genotypes discovered were present in two or more individuals. For both types of markers, AMOVA showed that most of the variation was within populations. Minor geographic pattern was confirmed by a Bayesian clustering analysis. Gene flow via pollen was found to be approximately 7 times more important than via seeds. Conclusions The data are consistent with outbreeding and indicate that there are no significant barriers for gene flow within Ireland over large geographic distances. Both pollen-mediated and seed-mediated gene flow were found to be high, with some of the populations being more than 200 km apart from each other. These findings could simply be due to human intervention through seed trade or accidental transportation of both seeds and pollen. These results are of value to breeders wishing to exploit natural genetic variation and foresters having to choose planting material.
PUBLISHED
Keywords: Genetic diversity; Microsatellites; Population structure; Salix; Willow; Genetic diversity; Microsatellites; Population structure; Salix; Willow; Genes & Society; Smart & Sustainable Planet; Bioenergy crops